A review of atmospheric vortex engines for power generation. Issue 230 (November 2022) - Leong, Khay-Wai; MacDonald, Michael; Cater, John E.; Flay, Richard G.J.
Abstract: A review has been conducted to understand buoyancy-induced vortex flow behaviour, establish control parameters, and to assess the possibility of harnessing kinetic energy in the flow for electricity production. To create and maintain a vortex, a buoyancy force generated by a relatively large heat flux over a large surface area is required, such that warmed air is concentrated at the centre and rise. This flow induces an inward swirl and large angular momentum. These two contributions need to overcome surface friction and ambient shear flow. A single-cell vortex possesses the highest energy flux to circulation strength ratio. Even though a two-cell vortex at the base corner possesses a higher incoming tangential velocity which would translate to a larger change in angular momentum for higher aerodynamic torque, it is less stable due to high shear between the core downdraft and peripheral updraft swirl. The atmospheric vortex engine should be designed and controlled such that the buoyancy vortex can be generated and anchored, the guide vanes and other vortex station features create minimal flow shear, and the vortex stability is minimally affected by the physical presence of the turbine, saturated steam, air influx and energy extraction. Highlights: Atmospheric vortex dynamics and structures defined using dimensionless parameters. Two-cell vortex has higher aerodynamic torque potential, but less stable. Power extraction from experimental and CFD vortex studies and proposals discussed.